PRODUCTION OF NEUTRAL STRANGE PARTICLES IN MUON-NUCLEON SCATTERING AT 490 GEV - Adams, M; Aderholz, M; Aid, S; Anthony, P; Baker, M; Bartlett, J; Bhatti, A; Braun, H; Busza, W; Conrad, J; Coutrakon, G; Davisson, R; et al. (1994)
The production of K0, Λ and Mathematical expression particles is studied in the E665 muon-nucleon experiment at Fermilab. The average multiplicities and squared transverse momenta are measured as a function of xF and W2. Most features of the data can be well described by the Lund model. Within this model, the data on the K0/π± ratios and on the average K0 multiplicity in the forward region favor a strangeness suppression factor s/u in the fragmentation process near 0.20. Clear evidence for QCD effects is seen in the average squared transverse momentum of K0 and Λ particles. © 1994 Springer-Verlag.